sFlT-1/PlGF ratio as a predictor of preeclampsia in COVID-19 pregnant patients - Kamil Pluta; Marcin Januszewski; Laura Ziuzia-Januszewska; Michał Kudan; Maria Suchocka; Kinga Kuśmierczuk; Tadeusz Issat; Artur J. Jakimiuk (BMC, 2024)
Abstract The association between SARS-CoV-2 infection in pregnancy and preeclampsia is widely debated in numerous studies. The aim of our study was to investigate whether an increased sFlt-1/PlGF ratio is a good marker of preeclampsia in pregnant patients with COVID-19 infection. This single centre prospective study was conducted in the Department of Obstetrics and Gynaecology, at the Central Clinical Hospital of the Ministry of the Interior and Administration in Warsaw. The study group consisted of 68 COVID-19 pregnant patients and 57 SARS-CoV-2 negative pregnant controls. Serum sFlt-1/PlGF ratio was assessed. The two groups did not differ in terms of the frequency of IVF, nulliparity, history of hypertension, pre-gestational diabetes and chronic kidney disease. The primary outcome was the diagnosis of preeclampsia. Preeclampsia was diagnosed in 10 patients in both groups. The sFlt-1/PlGF ratio higher than 38, considered highly suggestive of developing preeclampsia, was found in 20 patients in the COVID-19 group and 15 patients in the control group. The odds of developing preeclampsia in patients with sFlt-1/PlGF ratio > 38 was approximately 4-fold higher in COVID-19 group and 11-fold higher in controls. Sflt-1/PlGF ratio does not differ significantly between the SARS-CoV-2-positive and SARS-COV-2-negative pregnant patients. The sFlt-1/PlGF ratio > 38 is associated with higher odds of the diagnosis of preeclampsia in both of these groups, and therefore may serve as its marker regardless of COVID-19 infection status.